2021
DOI: 10.3390/cancers13071619
|View full text |Cite
|
Sign up to set email alerts
|

Deletions on Chromosome Y and Downregulation of the SRY Gene in Tumor Tissue Are Associated with Worse Survival of Glioblastoma Patients

Abstract: Background: Biological causes of sex disparity seen in the prevalence of cancer, including glioblastoma (GBM), remain poorly understood. One of the considered aspects is the involvement of the sex chromosomes, especially loss of chromosome Y (LOY). Methods: Tumors from 105 isocitrate dehydrogenase (IDH) wild type male GBM patients were tested with droplet digital PCR for copy number changes of ten genes on chromosome Y. Decreased gene expression, a proxy of gene loss, was then analyzed in 225 IDH wild type GBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…However, no significant sex-related differences in transcriptomes of gliomas have been observed [ 28 ], but it seems that the existing differences in survival are attributed to the role of the male sex chromosome in patients’ samples. It has been shown that deletion of the SRY gene, loss of genes located on the Y chromosome, and complete loss of the Y chromosome in GBM samples negatively influence the survival of male patients [ 29 ]. SRY/chromosome Y status might partially explain the mechanisms underlying the observed sex disparities regarding incidence, prognosis, drug toxicity, clinical outcome, and therapeutic response in GBM [ 30 ].…”
Section: The Role Of Sox Genes In Glioblastomamentioning
confidence: 99%
“…However, no significant sex-related differences in transcriptomes of gliomas have been observed [ 28 ], but it seems that the existing differences in survival are attributed to the role of the male sex chromosome in patients’ samples. It has been shown that deletion of the SRY gene, loss of genes located on the Y chromosome, and complete loss of the Y chromosome in GBM samples negatively influence the survival of male patients [ 29 ]. SRY/chromosome Y status might partially explain the mechanisms underlying the observed sex disparities regarding incidence, prognosis, drug toxicity, clinical outcome, and therapeutic response in GBM [ 30 ].…”
Section: The Role Of Sox Genes In Glioblastomamentioning
confidence: 99%